2021
DOI: 10.3389/fneur.2021.635032
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Characteristics in Pediatric Hereditary Spastic Paraplegia vs. Bilateral Spastic Cerebral Palsy: An Exploratory Study

Abstract: Hereditary spastic paraplegia (HSP) is a neurological, genetic disorder that predominantly presents with lower limb spasticity and muscle weakness. Pediatric pure HSP types with infancy or childhood symptom onset resemble in clinical presentation to children with bilateral spastic cerebral palsy (SCP). Hence, treatment approaches in these patient groups are analogous. Altered muscle characteristics, including reduced medial gastrocnemius (MG) muscle growth and hyperreflexia have been quantified in children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…In agreement with previous studies that applied ratio-scaling, muscle volume was normalized to body mass (Barber et al, 2011(Barber et al, , 2016De Beukelaer et al, 2021;Fry et al, 2007;Malaiya et al, 2007;McNee et al, 2009;Noble et al, 2014Noble et al, , 2017Noble et al, , 2019Obst, Bickell, et al, 2022;Pierce et al, 2012;Pitcher et al, 2018;Schless et al, 2018Schless et al, , 2019 .…”
Section: Statisticalanalysessupporting
confidence: 65%
See 1 more Smart Citation
“…In agreement with previous studies that applied ratio-scaling, muscle volume was normalized to body mass (Barber et al, 2011(Barber et al, , 2016De Beukelaer et al, 2021;Fry et al, 2007;Malaiya et al, 2007;McNee et al, 2009;Noble et al, 2014Noble et al, , 2017Noble et al, , 2019Obst, Bickell, et al, 2022;Pierce et al, 2012;Pitcher et al, 2018;Schless et al, 2018Schless et al, , 2019 .…”
Section: Statisticalanalysessupporting
confidence: 65%
“…Multiple studies in cerebral palsy have reported different ratio scaling methods. Muscle volume is often normalized to body mass (Barber et al, 2011(Barber et al, , 2016De Beukelaer et al, 2021;Fry et al, 2007;Malaiya et al, 2007;McNee et al, 2009;Noble et al, 2014Noble et al, , 2017Noble et al, , 2019Obst, Bickell, et al, 2022;Pierce et al, 2012;Pitcher et al, 2018;Schless et al, 2018Schless et al, , 2019, the product of body mass and height (De Beukelaer et al, 2022;Handsfield et al, 2016;Massaad et al, 2019;Obst et al, 2017) or bone length (Alexander et al, 2018;Haberfehlner et al, 2016;, whereas, Additionally, correlation coefficients were compared by a Steiger's Z-test to identify the most efficient scaling technique. The current results revealed that it is valid to describe muscle volume (with exception of the rectus femoris muscle) and muscle belly length alterations over age by a simple linear regression equation till the age of 11 years.…”
Section: Introductionmentioning
confidence: 99%
“…The current study created novel information that is relevant for different applications of the 3-D fUS technique. First, the data and training protocol provide a framework to study muscle morphology with 3-D fUS in several populations, including other patient groups that are characterized by spasticity, such as hereditary spastic paraplegia (De Beukelaer et al 2021) and stroke (Schillebeeckx et al 2020); pediatric populations with other underlying causes of disability, such as neuromuscular disorders or clubfoot; athletes with muscular injuries; and the elderly to study the effects of sarcopenia (Watanabe et al 2013). In the view of future use of the current study findings for other populations, it should be noted that when the 3-D fUS technique is applied for larger muscles, for example, in adults or dystrophic pseudo-hypertrophic muscles, a good calibration for multiple parallel sweep data collection is a prerequisite (Cenni et al 2019), which may also require additional processing guidelines.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Hereditary spastic paraplegias (HSPs) are a myriad of monogenic neurological defects aiding corticospinal and dorsal spinal cord axonal atrophy with a prevalence of 0.1-9.6 instances in every 100,000 around the world [1]. The critical manifestations include lower extremity bilateral spasticity, overactive reflexes, extensor plantar reflex, muscle fragility, and triggered gait deviations [2]. HSPs legacies are seen in almost all inheritance patterns, namely autosomal dominant (AD), autosomal recessive (AR), X-linked recessive (XLR), and mitochondrial, with about >80 susceptible gene loci registered to date [3,4].…”
Section: Introductionmentioning
confidence: 99%